Eastern Anatolıa Regıon Wıth Respect To Tourısm Based Development - Gunduz, Ali Yilmaz (Advances in Social Sciences Research Journal, 2019)
Significant developments and changes happened in economic, technological, political, social and cultural fields in recent years crucially affected tourism sector/segment. Despite the fact that Turkey, which possesses a majör potential with rich cultural, historical and natural values, has a remarkable advantage in terms of tourism, it couldn't enjoy this advantage for long years. Development of tourism sector/segment in Turkey is encountered in post 1980 era. In this era Tourism Incentive Law, taking decisions regarding Promotion of Foreign Exchange Earning Services and Businesses, enactment of Foreign Capital Law, decisions taken on the subject of bending law no. 31, Protection Order of Turkish Currency Value became crucial factors in development of tourism. As a result of these decisions taken, tourism income, which was 326 million USD in 1980, has risen up to 35 billion USD in 2017. Tourism's share in GDP has risen from %0.6 to the level of %4 for the same years. Tourism sector/segment is gaining greater importance in decreasing regional derangement/conflict, developing of underdeveloped regions which lack sufficent resources and opportunities for agriculture and industrial sector on the other hand have rich tourism potential. Main purpose of this research is measuring potiential usability of Eastern Anatolia Region, which has a unique beauty in terms of tourism, so much the more Hakkari zone and providing recognisability by destroying negative image of this zone.